Pemetaan Komponen Metabolit Sekunder Utama dari Tanaman Berkhasiat terhadap Paru paru menurut Al-Qanun fi at-Tibb 2 karya Ibnu Sina - djamain, nelly suryani; Nurkholiza, Zahara Faiziah; Saibi, Yardi Yardi; Betha, Ofa Suzanti; Dahlizar, Sabrina Sabrina; Dillasari, Estu Mahanani (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2024)
Al-Qanun fii at-Tibb 2 is a medical text book by Ibn Sina, which contains monographs of various natural materials, especially plants that have properties for organs including the lungs. In this book there is no data regarding the secondary metabolite content of these plants and this study aims to conduct a literature review of the main secondary metabolite components of these plants. and see the correlation between the major components and their efficacy on the lungs. This research was conducted using the literature review method through various databases by extracting from 124 scientific journals information about 58 plants that are efficacious for lung organs according to Al Qanun Fi'l Tibb and data has been produced in the form of the content of the main secondary metabolites of these plants, namely flavonoids, terpenes, tannins, lignans., saponins, anthraquinones, glucosinolates, phenolic acids, sekoiridoids, steroids, and alkaloids as the major components. Based on the results of this review, the main components of secondary metabolites are known to have reported beneficial bioactivities in the treatment of the respiratory system and lung organ.